Структурная скрытность линейных сигналов широкополосных XDSL технологий - Шинкаренко, И. В.; Цопа, А. И. (ХНУРЭ, 2011)
This report presents assess of structural secrecy linear signals of digital communication’s systems based on xDSL technology. We obtain formulas for calculating the structural secrecy of different options of linear signals and examined ways to improve the potential of structural secrecy.
Keywords: ведомственные системы связи; скрытность системы связи